Effect of post-diagnosis exercise on depression symptoms, physical functioning and mortality in breast cancer survivors: A systematic review and meta-analysis of randomized control trials. (April 2022) - Salam, Abdul; Woodman, Alexander; Chu, Ashely; Al-Jamea, Lamiaa H.; Islam, Mohammed; Sagher, Malek; Sager, Mohammed; Akhtar, Mahmood
Abstract: Background: Cancer is the second leading cause of death worldwide. Breast cancer, the most common cancer found in women, affects 2.1 million women annually and has the highest number of cancer related deaths. The objective of the current meta-analysis is to evaluate the effects of post-diagnosis exercises on depression, physical functioning, and mortality in breast cancer survivors. Methods: The search for eligible articles was conducted through CINAHL, Medline/PubMed, Scopus, Cochrane, Emerald Insight and Web of Science, Embase database, MEDLINE In-Process, Elsevier, Google Scholar, PsycInfo, Cochrane Database of Systematic Reviews (CDSR), Cochrane Central Register of Controlled Trials (CENTRAL), Allied and Complementary Medicine (AMED), Biosis Previews, SPORTDiscus, PEDro scientific databases from 1974 to 2020. Following the exclusion procedure, 26 articles yielded for final analysis. The combined statistics for depression, physical functioning, and mortality in breast cancer survivors were calculated using standardized mean differences (SMD). Standard errors and 95% confidence intervals (CI) were converted to standard deviations as required. For mortality, combined statistics were calculated using hazard ratios (HR). The 95% CIs were converted to standard errors as required. The forest plots display point estimates and 95% CIs. Results: Statistically significant improvements on levels of depression were identified following the exercise intervention, suggesting that post-diagnosis physical activity leads to a decrease in depression scores. Overall, post-diagnosis exercise led to a 37% reduction in the rate of breast cancer-specific mortality. The all-cause mortality rate was decreased by 39% with the inclusion of moderate physical activity as the part of daily routine. Conclusions: Future studies should look at how to improve the quality of life while incorporating physical activity as a daily routine after breast-cancer treatment. Highlights: Women diagnosed with breast cancer experience the long-term physical and psychosocial effects of cancer and its treatment. Sadness, depression, sleep, appetite changes, decreased quality of life are considered as the side effects of treatment. Physical activity is statistically significant in reducing the risk of all-cause mortality, breast cancer-specific mortality. There were statistically significant improvements in depression levels in patients who were physically active post-diagnosis. Future studies are expected to investigate the long-term effects of exercise on the health of breast cancer survivors.